ظاهرة تضخيم نقاط التقويم المستمر في التعليم المتوسط وأثره على التوجيه المدرسي - عزوز, حمزة (جامعة الوادي - University of Eloued, 2020)
تناولنا في هذه الدراسة ظاهرة تضخيم نقاط التقويم المستمر في التعليم المتوسط وأثاره على المسار الدراسي للتلاميذ. ولتحقيق هذه الدراسة، اعتمدنا المنهج الوصفي وذلك لمعرفة ما إذا كانت هذه الظاهرة موجودة فعلا في مؤسساتنا التعليمية. كما وظفنا المنهج الإحصائي للكشف عن حدتها. كأدوات لجمع البيانات، اعتمدنا المقابلة نصف الموجهة للتعرف أكثر على ميدان الدراسة. أخيرا وظفنا الاستمارة للكشف عن أسباب اختيار التلاميذ للجذع المشترك الذي يزاولـون الدراسة فيه، رغم تعـرض علاماتهــم في التقويم المستمر إلى التضخيم في التنقيط وضعف نتائجهم في المواد الأساسية المشكلة لمجموعة التوجيه في امتحان شهادة التعليم المتوسط. النتائج المتوصل إليها أفضت إلى تأكيد وجود ظاهرة التضخيم في في علامات معظم المواد المشكلة للملمح الأدبي وحتى بعض المواد المشكلة للملمح العلمي. ما قد يؤثر سلبا على المسار الدراسي لهؤلاء التلاميذ في مرحلة التعليم الثانوي و ينجر عنها إخفاق في امتحان شهادة البكالوريا. Abstract:This study deals with the phenomenon of overnotation continuous evaluation at the intermediate level and its effects on students' academic background. Initially, to verify the existence of this practice in our colleges, we used the descriptive method. Then, to measure the extent of this phenomenon, we used the statistical method. To collect the information needed for this research and to better understand the field of study, we used semi-directive interview as a tool. Finally, we used a questionnaire, the purpose of which was to discover the reasons that led students to choose a particular common core, despite the over-rating on the continuous evaluation t and the low results in the main subjects that make up the orientation group in the final junior exam. The results obtained confirmed the existence of the phenomenon of overnotation in almost all the subjects that make up the literary profile, and in some subjects that make up the scientific and technological profile. This could have a negative effect on the school curriculum of these pupils in secondary education and lead to failure in the baccalaureate.
مقال
Keywords: تضخيم ; النقاط ; - ; التق ; يم ; المستمر ; مجم ; عة ; الت ; جيه ; التزج ; ملمح ; التجيه ; -المسار ; الدراسي; Continuous evaluation; Guidance group; Guidance profile; The School cursus